2010
DOI: 10.5650/jos.59.395
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Limonene on Permeation Enhancement of Ketoprofen in Palm Oil Esters Nanoemulsion

Abstract: This study sets out to investigate the in vitro permeation of ketoprofen from the formulated nanoemulsions through excised rat skin. In vitro permeation of ketoprofen nanoemulsion through rat skin was evaluated in Franz diffusion cells and compared with marketed product Fastum gel ® . Limonene which has been reported to be a good enhancer for ketoprofen was selected. Moreover the effects of limonene which was added to the nanoemulsion formulations at levels of 1%, 2%, 3% and on rat skin permeation of ketoprofe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 23 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Additionally, some authors have demonstrated that limonene can exert a protective effect against diabetes in a treatment experimental model using rats [ 16 ]. Moreover, limonene increases the permeation of other drugs, both in in vitro and in vivo models [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some authors have demonstrated that limonene can exert a protective effect against diabetes in a treatment experimental model using rats [ 16 ]. Moreover, limonene increases the permeation of other drugs, both in in vitro and in vivo models [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The literature reports various approaches such as the use of bile salts, saponins [1] , straight chain fatty acids [2] , microemulsion [3] , nanoemulsion [4] , cyclodextrin inclusion complex [5] , chitosan derivatives [6] , self-micro-emulsifying drug delivery systems [7] , interfacial cohesion and supramolecular assembly of bioadhesive species [8] (including liquid crystals) for permeation enhancement of BCS-III drugs [9] . Additionally, advanced technologies, such as iontophoresis [10] , ultrasound [11] , microneedles [12] , [13] , electroporation [14] , radiofrequency [15] , and microporation [16] have been used for enhancing the transdermal permeation of drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the RSV partition coefficient (LogP = 3.09) [31] and good solubility in lipid excipients allow its use to generate formulations that rely on solid lipid microparticles (SLM). The latter are also ideal to encapsulate extremely volatile substances, such as LIM, considering that essential oils extracted from Citrus species containing a high percentage of LIM (85%) were shown to have antimicrobial effects against acne-inducing bacteria [32], as well as to promote the absorption of other substances through the human skin and mucous membrane [33,34]. Thus, SLMs containing RSV and LIM are here proposed as an innovative formulation capable of exerting a synergistic antimicrobial efficacy, which might promote the absorption of various drugs.…”
Section: Resultsmentioning
confidence: 99%